Media Literacy: Advantages and Applications A Case Study of Chinese Student of Nakhon Pathom Rajabhat University - Buawech, Yaowapa; Sarbmuangpak, Tivaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research aimed 1) to investigate the advantages of Chinese students’ media literacy and 2) to examine how Chinese students apply media literacy. The respondents were nineteen Chinese students from Nanning College for Vocational Technology, China. They were studying in the Thai writing subject of the Thai language for communication course at Nakhon Pathom Rajabhat University in the academic year 2018. The research was conducted by non-probability sampling and the respondents were selected by purposive sampling. Before a set of survey used as a research instrument, it had been developed based on the conceptual framework to collect data from the research samples and follow the purposes of the study. The program was used to calculate the statistics and the descriptive statistics including frequency, percentage, means and standard deviation were used to analyze the data. The findings were that 1) the means of the advantages of Chinese students’ media literacy was high in both overall and individual items (µ = 4.50, σ = 0.66) and 2) the means of the applications on Chinese students’ media literacy was high in both overall and individual items. (µ = 4.35, σ = 0.76) Article history : Received 24 April 2019 Revised 10 June 2019 Accepted 12 June 2019 SIMILARITY INDEX = 1.22 %